Translations of Responsibility Innovation Governance in Three European Regions - Völker, Thomas (History and Philosophy of Technoscience, 2024)
In 2020, a group of European researchers got a European Union (EU) grant to do a project called TRANSFORM. The objective of TRANSFORM was to integrate the principle of responsible research and innovation (RRI) into the research and innovation policies of three European regions: Lombardy, Brussels, and Catalonia. This book tells the story of how TRANSFORM translated RRI into practice, all the way from philosophy of technology to EU policy jargon, to the project contract, and finally into the real-life events in these regions. Responsibility was translated in creative ways, with surprising goals and ambiguous outcomes. Armed with these stories, the book analyses the broader context of the desire for better governance of technoscience and draws two lessons: Firstly, that there is more governance than one may see at first sight, and secondly, that there is a need to rethink the borders of technoscience and the spaces in which it resides. The book proposes to think of governance in technoscience, rather than governance of technoscience.